Composite material for secondary lithium ion battery as well as preparation method and application of composite material
By using a porous matrix carrier in lithium-ion batteries to uniformly disperse hydrogen-containing silicon and form a shell layer, the problems of nano-silicon dispersion and activity are solved, the battery cycle life is extended and the electrochemical performance is improved.
Patent Information
- Application Number
- CN202411395650.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-11-14
AI Technical Summary
Silicon nanoification technology in lithium-ion batteries has volume expansion effects caused by uneven dispersion and agglomeration of nano-silicon particles, which affects the integrity of the electrode structure and electrochemical performance. The high nano-silicon activity leads to lithium ion consumption and safety problems.
The porous matrix is used as a carrier, and hydrogen-containing silicon is uniformly dispersed by CVD deposition and liquid impregnation, and a dense shell layer is formed on the outer surface to avoid oxidation of highly active nano hydrogen-containing silicone and contact with the electrolyte to form a stable solid electrolyte interface film.
It effectively solves the volume expansion problem caused by silicon dispersion and agglomeration, extends the battery cycle life, improves electrochemical performance and safety, and improves the charging and discharge stability and capacity retention rate of lithium-ion batteries.
Smart Images

Figure CN119275269A_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application No. 202311513274.6, filed on November 14, 2023, entitled “A composite material for secondary lithium-ion batteries, its preparation method and application”. Technical Field
[0002] The present invention relates to the technical field of batteries, and in particular to a composite material for secondary lithium-ion batteries and a preparation method and application thereof. Background Art
[0003] Lithium-ion batteries are one of the most widely used secondary battery systems. Compared with other rechargeable batteries such as nickel-cadmium batteries and nickel-metal hydride batteries, lithium-ion batteries have the characteristics of high energy density, high operating voltage, limited self-discharge, and low maintenance requirements. However, commercial graphite anodes have only 372 mAhg -1 The theoretical specific capacity cannot meet the increasing demands of portable electronic devices, electric vehicles and energy storage applications for energy density, operation reliability and system integration.
[0004] Among all potential lithium-ion battery anode materials, silicon is one of the most promising candidates to replace graphite for the following reasons: (1) Silicon has the highest weight-to-weight capacity (4200 mAh g -1 ) and volumetric capacity (9786mAhcm -3 ); (2) The discharge voltage of Si is about 0.4 V on average, which strikes a good balance between maintaining a reasonable open circuit voltage and avoiding unfavorable lithium plating processes; (3) Silicon reserves are abundant (the second highest content in the earth's crust) and are potentially low-cost, environmentally friendly, and non-toxic.
[0005] However, as silicon inserts and removes lithium, its volume expands and contracts rapidly (volume change is about 360%) and generates huge stress, which has a series of serious effects on the structure: (1) During repeated charge and discharge, the integrity of the electrode structure is destroyed; (2) The interface stress induces the disconnection of the electrode from the current collector; (3) The solid electrolyte interface (SEI) layer causes lithium ions to be continuously consumed during the continuous formation-rupture-reformation process. These processes will accelerate electrode collapse and capacity decay in a synergistic manner. In addition, the poor intrinsic electronic conductivity of silicon is also the reason for the slow electrochemical kinetics.
[0006] Silicon nanotechnology can effectively alleviate the impact of the above problems. CN 116454256A discloses a method for preparing a silicon-carbon composite material, wherein nano-silicon and nano-carbon are directly used for in-situ compounding, and then coated with a layer of carbon material; and a micron-level silicon-carbon composite material is obtained by spray granulation of a slurry; a high-temperature treatment is used to pyrolyze the binder or other impurities in the slurry to form pores, which provide expansion space for silicon, and the conductive carbon improves the conductivity of the material itself, which is conducive to the performance of electrochemical performance.
[0007] Nano-sizing of silicon can effectively alleviate the effect of volume expansion on electrodes, but the dispersion of nano-silicon particles and carbon materials still faces great difficulties. The agglomeration of nano-silicon will still lead to volume expansion effect, which cannot give full play to the advantages of nano-silicon. Summary of the invention
[0008] The invention provides a composite material for a secondary lithium ion battery and a preparation method and application thereof, so as to solve the problems faced by nano silicon in the secondary lithium ion battery.
[0009] In one aspect, the present invention relates to a composite material for a secondary lithium ion battery, the composite material comprising: a porous matrix, hydrogen-containing silicon dispersed in the porous matrix, and a shell layer coated on the outer surface of the porous matrix.
[0010] In one embodiment, in the composite material, the hydrogen content in the hydrogen-containing silicon is 0.01-10 wt %, preferably 0.03-5 wt %, more preferably 0.09-3 wt %, based on the total weight of the composite material.
[0011] On the other hand, the present invention relates to a method for preparing the composite material of the present invention, which comprises the following steps: providing a porous matrix; forming hydrogenated silicon dispersed in the porous matrix by CVD deposition and / or liquid impregnation; and coating the outer surface of the porous matrix in which the hydrogenated silicon is dispersed to form a shell layer.
[0012] In another aspect, the present invention relates to a negative electrode sheet, comprising the composite material of the present invention.
[0013] In another aspect, the present invention relates to a lithium ion secondary battery, comprising the negative electrode sheet of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 : (a) infrared spectrum of the composite material sample of Example 1; (b) infrared spectrum of the composite material sample of Example 2; (c) infrared spectrum of the composite material sample of Example 3; (d) infrared spectrum of the composite material sample of Example 4; (e) infrared spectrum of the composite material sample of Example 5; (f) infrared spectrum of the composite material sample of Example 6; (g) infrared spectrum of the composite material sample of Example 7.
[0015] Figure 2 : XRD spectrum of the composite material sample of Example 1.
[0016] Figure 3 : (a) SEM image of the composite material sample of Example 1; (b) TEM image of the composite material sample of Example 1.
[0017] Figure 4 : The charge and discharge curves of the button-type half-cell obtained by assembling the negative electrode sheet prepared from the composite material sample of Example 1.
[0018] Figure 5 : Cycling curves of button-type full batteries obtained by assembling negative electrode sheets prepared from the composite material samples of Examples 1-7.
[0019] Figure 6 : Cycling curve of button-type full battery obtained by assembling the negative electrode sheet prepared from the composite material sample of Example 1.
[0020] Figure 7 : Thickness expansion curve of button-type full battery obtained by assembling the negative electrode sheet prepared from the composite material sample of Example 1. DETAILED DESCRIPTION
[0021] General Definitions and Terminology
[0022] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. In case of conflict, the definitions in the present specification shall prevail.
[0024] Unless otherwise indicated, all percentages, parts, ratios, etc. are based on weight.
[0025] When providing quantity, concentration or other value or parameter as range, preferred range or preferred upper limit and lower limit or specific value, it should be understood as specifically disclosing all ranges formed by paired values from any upper limit range or preferred value and any lower limit range or preferred value, regardless of whether the range is disclosed individually. Unless otherwise stated, when numerical range is quoted herein, described range refers to including its endpoints and integers and fractions within all such ranges. The scope of the present invention is not limited to the specific numerical value quoted when defining the range.
[0026] When values or end-points of a range are described herein, it should be understood that the disclosure includes the specific value or end-point cited.
[0027] The expression "comprising" or its synonymous similar expressions "including", "containing" and "having" etc. are open-ended and do not exclude additional unrecited elements, steps or ingredients. The expression "consisting of excludes any element, step or ingredient not specified. The expression "consisting essentially of means that the scope is limited to the specified elements, steps or ingredients, plus the optional elements, steps or ingredients that do not materially affect the basic and novel characteristics of the claimed subject matter. It should be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".
[0028] Unless otherwise stated, the term "a combination thereof" means a multi-component mixture of the elements mentioned, for example a mixture of two, three, four and up to the maximum possible multi-component mixture.
[0029] In addition, if the number of parts or components of the present invention is not indicated before, it means that there is no limit to the number of occurrences (or existence) of the parts or components. Therefore, it should be interpreted as including one or at least one, and the singular form of the parts or components also includes the plural form, unless the numerical value obviously represents the singular.
[0030] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes both occurring and not occurring of said event or circumstance.
[0031] As used herein, the terms "one or more" or "at least one" means one, two, three, four, five, six, seven, eight, nine or more.
[0032] "Carbon" refers to a material or substance that essentially includes carbon. Examples of carbon materials include, but are not limited to, activated carbon, pyrolytic carbon, hard carbon, graphite, and other allotropes of carbon.
[0033] "Carbonize," "pyrolyze," "carbonization," and "pyrolysis" all refer to the process of heating a carbonaceous material at a pyrolysis soak temperature in an inert atmosphere (e.g., argon or nitrogen) or in a vacuum so that the target material collected at the end of the process is primarily carbon. "Pyrolyzed" refers to a material or substance (e.g., a carbon material) that has undergone a pyrolysis process.
[0034] "Soaking temperature" refers to the temperature of the furnace during the portion of the process reserved for maintaining a relatively constant temperature (i.e., not increasing or decreasing the temperature). For example, the pyrolysis soaking temperature refers to the relatively constant furnace temperature during the pyrolysis process, and the activation soaking temperature refers to the relatively constant furnace temperature during the activation process.
[0035] "Pore structure" refers to the surface layout of internal pores in a carbon material (e.g., an activated carbon material). The composition of the pore structure includes pore size, pore volume, surface area, density, pore size distribution, and pore length. Typically, the pore structure of a porous carbon material includes micropores, mesopores, and macropores.
[0036] "Mesopores" refer to pores with a pore size of 2-50nm, "micropores" refer to pores with a pore size less than 2nm, and "macroporous" refers to pores with a pore size greater than 50nm. Mesoporous carbon materials have mesopores that account for more than 50% of the total pore volume. Microporous carbon materials have micropores that account for more than 50% of the total pore volume.
[0037] "Surface area" refers to the total specific surface area of a substance that can be measured by the BET technique. Usually, surface area is measured in m 2 The BET technique uses an inert gas (such as nitrogen) to measure the amount of gas adsorbed on a material and is commonly used in the art to determine the accessible surface area of a material.
[0038] A "composite material" refers to a composition comprising multiple (2 or more) different chemical species within the same particle, such as a particle comprising a porous carbon material and a silicon material.
[0039] "Allotropes" refers to materials that are composed of the same single chemical element but can exist in different forms. C60, graphene, diamond, hard carbon, soft carbon, graphite, and carbon nanotubes are all examples of carbon allotropes. "Hard carbon" refers to non-graphitizing carbon materials. At high temperatures (typically 1500-2200°C), hard carbon remains essentially amorphous, while soft carbon will undergo crystallization and become graphitized.
[0040] "Coulombic efficiency" refers to the ratio of the discharge capacity to the charge capacity of a lithium-ion energy storage device. Coulombic efficiency is a percentage or fraction (for example, 99% = 0.99).
[0041] Composite materials for secondary lithium-ion batteries
[0042] In one aspect, the present invention provides a composite material for a secondary lithium ion battery, the composite material comprising: a porous matrix, hydrogenated silicon dispersed in the porous matrix, and a shell layer coated on the outer surface of the porous matrix.
[0043] Porous matrix
[0044] The porous matrix of the present application has a suitable pore structure, which is conducive to the uniform dispersion of silicon particles in the inner pores of the porous matrix to form nano silicon particles, thereby avoiding the volume expansion effect that may occur due to the agglomeration of silicon particles, thereby giving full play to the advantages of nano silicon particles and improving the performance of the composite material.
[0045] In the present invention, the porous matrix can be made of various materials, including but not limited to porous carbon, porous polymer materials, porous ceramic materials, porous metal materials or a combination thereof.
[0046] In a preferred embodiment, the porous matrix material mainly comprises carbon, such as hard carbon. Other allotropes of carbon are also conceivable, such as graphite, amorphous carbon, diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene and / or carbon fiber. Porosity can be introduced into the carbon material in various ways. For example, the porosity in the carbon material can be achieved by adjusting polymer precursors and / or processing conditions to produce porous carbon materials (described in detail in subsequent parts).
[0047] In other embodiments, the porous matrix may include polymer materials. Polymers include, but are not limited to, at least one of polyaniline, polyether, polytetrafluoroethylene, polyethylene oxide, chitosan, polyvinyl alcohol, polyacrylamide, microcrystalline cellulose, polystyrene, 3,4-ethylenedioxythiophene, styrene sulfonate, polyethyleneimine, polyurethane, aqueous polyurethane, polyimide, hydrated aramid nanofiber, polydimethylsiloxane, acrylonitrile-butadiene-styrene, polyethersulfone, and polycarbonate polyacrylonitrile. Polymers also include resin materials, such as epoxy resins, polyester resins, acrylic resins, phenolic resins, FEVE fluororesins, ETFE fluororesins, phthalonitrile resins, etc. Polymers may also include biomass materials: lignin, coconut shells, bamboo, fructose, sucrose, maltose, glucose, cellulose, and starch, etc.
[0048] The porous matrix material includes porous ceramic materials, including but not limited to porous magnesium oxide, porous aluminum oxide, porous beryllium oxide, porous zirconium oxide, porous tin oxide, porous silicon dioxide, porous silicon nitride, porous aluminum nitride, porous boron nitride, porous titanium nitride, and porous silicon carbide.
[0049] Porous matrix materials also include porous metals, including but not limited to porous aluminum, porous steel, porous nickel, porous nickel, porous Inconel, porous titanium, porous copper, porous brass, porous gold, porous silver, porous germanium, and the like.
[0050] In the present invention, the preparation of porous materials includes but is not limited to the following methods: emulsification, micelle generation, gasification, dissolution followed by solvent removal (e.g., freeze drying), axial compaction and sintering, gravity sintering, powder rolling and sintering, isostatic compaction and sintering, metal spraying, metal coating and sintering, metal injection molding and sintering, etc. The preparation method of porous materials may also include other ways to produce porous polymer materials, including producing porous gels, such as freeze-dried gels, etc.
[0051] The particle size of the silicon particles dispersed in the pores of the porous matrix is affected by the pore size distribution of the porous matrix. A suitable pore size distribution of the porous matrix helps to promote the formation of nano silicon particles. The porous matrix can contain 20%-90% micropores, 10%-50% mesopores and 0-30% macropores. The total pore volume of the porous matrix can be 0.1-2.5cm 3 / g, preferably 0.5-1.2cm 3 / g.
[0052] In some embodiments, the porous carbon has a different pore size distribution, including 20% micropores, 50% mesopores, and 30% macropores, with a total pore volume of 1.2 cm 3 In some embodiments, the total pore volume is 1.0 cm 3 In some embodiments, the total pore volume is 0.9 cm 3 In some embodiments, the total pore volume is 0.8 cm 3 In some embodiments, the total pore volume is 0.7 cm 3 In some embodiments, the total pore volume is 0.6 cm 3 In some embodiments, the total pore volume is 0.5 cm 3 In some embodiments, the total pore volume is 0.4 cm 3 In some embodiments, the total pore volume is 0.2 cm 3 In some embodiments, the total pore volume is 0.1 cm 3 / g.
[0053] The appropriate pore volume of the porous matrix is conducive to increasing the silicon content in the composite material, thereby improving the performance of the corresponding product, such as the charge capacity. The specific surface area of the porous matrix can be 1000-2500m 2 / g, for example, 1900-2000m 2 / g, 1000-1200m 2 / g, 1500-1600m 2 / g, 2200-2500m 2 / g, etc.
[0054] The appropriate particle size distribution of the porous matrix is conducive to increasing the silicon content in the composite material, thereby improving the performance of the corresponding product. The D50 particle size of the porous matrix can be 1-30 μm, preferably 1-20 μm, for example, 5-15 μm, 5-20 μm, 10-25 μm, 5-25 μm, 10-30 μm, etc. The D100 particle size of the porous matrix can be 5-80 μm, preferably 5-50 μm, for example, 10-20 μm, 20-40 μm, 30-50 μm, 40-60 μm, 50-70 μm, 60-80 μm, etc.
[0055] In some embodiments, the particle size distribution of porous carbon is different, the particle size distribution D50 is 1-10 μm, and D100 is 5-10 μm. In certain embodiments, the particle size distribution D50 is 5-15 μm, and D100 is 10-20 μm. In certain embodiments, the particle size distribution D50 is 5-20 μm, and D100 is 20-40 μm. In certain embodiments, the particle size distribution D50 is 10-25 μm, and D100 is 30-50 μm. In certain embodiments, the particle size distribution D50 is 5-25 μm, and D100 is 40-60 μm. In certain embodiments, the particle size distribution D50 is 10-30 μm, and D100 is 50-70 μm. In certain embodiments, the particle size distribution D50 is 15-30 μm, and D100 is 60-80 μm.
[0056] The appropriate oxygen content of the porous matrix helps to improve the electrochemical performance of the product. If the oxygen content of the porous matrix is too high, it may lead to a decrease in the first coulombic efficiency of the battery. The oxygen content of the porous matrix can be 0.01-0.6 mmol / g, such as 0.01-0.4 mmol / g, 0.1-0.3 mmol / g, 0.2-0.5 mmol / g, 0.3-0.6 mmol / g, etc.
[0057] The tap density of the porous matrix can be 0.2-0.6 g / cm 3 , for example 0.2g / cm 3 , 0.3g / cm 3 , 0.4g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 In some embodiments, the tap density of the composite material for the secondary lithium ion battery is 0.8 g / cm 3 The tap density of the porous matrix is 0.4 g / cm 3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 1.2 g / cm 3 The tap density of the porous matrix is 0.5 g / cm3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 1.4 g / cm 3 The tap density of the porous matrix is 0.6 g / cm 3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 2 g / cm 3 The tap density of the porous matrix is 0.6 g / cm 3 .
[0058] Hydrogenated Silicon
[0059] In the present application, silicon is uniformly dispersed in the internal pores of the porous matrix to form nano silicon (i.e., nano silicon particles), while the outer surface of the porous substrate is substantially free of silicon, which is conducive to the material giving full play to the advantages of nano silicon. In the present application, for the silicon dispersed in the porous matrix, it retains some Si-H bonds, and thus the silicon dispersed in the porous matrix is also referred to as hydrogenated silicon.
[0060] The hydrogen-containing silicon in this application refers to: all nano-silicon dispersed in a porous matrix. In the hydrogen-containing silicon herein, at least a portion of the nano-silicon particles are nano-silicon particles with Si-H bonds.
[0061] The presence of Si-H bonds in hydrogenated silicon can effectively improve the stability of the composite material during the charge and discharge process and extend the battery cycle life. The Si-H bonds in hydrogenated silicon can be determined by any method in the art, including but not limited to infrared testing. The infrared spectrum of the composite material of the present application is at 625-640 cm -1 The infrared spectrum of the composite material may also have vibration peaks at one or more of the following positions: 845-885cm -1 1990-2010cm -1 .
[0062] "Hydrogen content in hydrogenated silicon" refers to the percentage of the total weight of H elements in the retained Si-H bonds in hydrogenated silicon to the overall weight of the composite material. There is a positive correlation between the amount of Si-H bonds in hydrogenated silicon and the hydrogen content in hydrogenated silicon. Factors such as the structure of the porous matrix and the dispersion process of silicon in the porous matrix will affect the amount of Si-H bonds in hydrogenated silicon and the hydrogen content in hydrogenated silicon. A suitable hydrogen content in hydrogenated silicon helps improve the electrical properties of the product, such as improving the capacity retention rate of the battery. Based on the total weight of the composite material, the hydrogen content in the hydrogen-containing silicon may be 0.01-10wt%, preferably 0.3-5wt%, more preferably 0.9-3wt%, for example, 0.01wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 5.0wt%, 10.0wt%, etc. The hydrogen content in the hydrogen-containing silicon may be determined by any method available in the art, for example, the hydrogen content C in the hydrogen-containing silicon H The infrared absorption peak in the rocking mode region during infrared testing can be used for fitting calculations.
[0063] The ratio of silicon dispersed in the porous matrix to the porous matrix also affects the performance of the composite material. The appropriate content of silicon dispersed in the porous matrix can give the product better electrical properties (such as excellent charge capacity), and can also retain some pores in the porous matrix to reserve a certain space for the expansion of silicon in the later stage, thus avoiding the composite material from breaking or even crushing due to the volume expansion of silicon.
[0064] Based on the total weight of the composite material, the silicon content of the composite material may be 5-90wt%, preferably 15-70wt%, more preferably 30-65wt%, for example 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%,
[0065] 35wt%, 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%,
[0066] 48wt%, 49wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%,
[0067] 85wt%, 90wt%, etc. It can be understood that when, in the composite material, except for the hydrogenated silicon dispersed in the porous matrix, if the composition of other parts (such as the porous matrix, the shell layer) does not contain Si, the silicon content in the composite material is the content of silicon dispersed in the porous matrix.
[0068] The appropriate particle size of hydrogen-containing silicon is beneficial to the improvement of the performance of the composite material. The particle size of hydrogen-containing silicon ranges from 0.1 to 60 nm, preferably from 0.1 to 20 nm, and more preferably from 1 to 5 nm.
[0069] The form of hydrogen-containing silicon can be crystalline silicon or amorphous silicon. In certain embodiments, hydrogen-containing silicon includes hydrogen-containing crystalline silicon. In certain embodiments, hydrogen-containing silicon includes hydrogen-containing polycrystalline silicon. In certain embodiments, hydrogen-containing silicon includes nano hydrogen-containing polycrystalline silicon. In certain other embodiments, hydrogen-containing silicon includes hydrogen-containing amorphous silicon. In certain other embodiments, hydrogen-containing silicon includes hydrogen-containing crystalline silicon and hydrogen-containing amorphous silicon.
[0070] The degree of crystallinity of silicon in hydrogen-containing silicon can be determined by any method in the art, such as by electrochemical curve. For the test sample obtained from the composite material, the platform of the charging curve at 0.4-0.5V and the characteristic peak of the corresponding DQ / DV curve at 0.4-0.5V are related to the degree of crystallinity of hydrogen-containing silicon. In hydrogen-containing silicon, the higher the proportion of crystalline silicon, the more obvious the platform of the charging curve at 0.4-0.5V, and the stronger the characteristic peak intensity of the DQ / DV curve at 0.4-0.5V.
[0071] Shell layer coated on the outer surface of porous substrate
[0072] The outer surface of the porous matrix also contains a dense shell layer, which serves as the outer layer of the composite material. The shell layer coated on the outer surface of the porous matrix can not only prevent the highly active nano hydrogen-containing silicon in the pores of the porous matrix from being oxidized and spontaneously combusted in the air, but also ensure that the porous matrix and the hydrogen-containing silicon inside it do not directly contact the electrolyte during the use of the composite material, which is conducive to the formation of a stable SEI film.
[0073] The shell layer may be formed by subjecting a porous matrix in which hydrogen-containing silicon is dispersed to a reaction treatment, or by attaching another material to the surface of the porous matrix.
[0074] The components of the shell layer may include, but are not limited to, amorphous carbon, graphene, carbon nanotubes, conductive polymers, titanium carbide, aluminum oxide, aluminum nitride, silicon carbide, silicon nitride, silicon oxide (such as silicon dioxide), silicon oxynitride or a combination thereof. In certain embodiments, the shell layer of the composite material of the present invention is a carbon shell.
[0075] The shell layer can be a single layer or multiple layers. Any layer in the shell layer may not be limited to one of the above-mentioned components, but may be a combination of several substances.
[0076] The appropriate thickness of the shell helps to give full play to the role of the shell. The thickness of the shell can be 1-1000nm. In some embodiments, the shell thickness of the composite material of the secondary lithium ion battery is 1-10nm. In certain embodiments, the shell thickness of the composite material of the secondary lithium ion battery is 10-50nm. In certain embodiments, the shell thickness of the composite material of the secondary lithium ion battery is 50-100nm. In certain embodiments, the shell thickness of the composite material of the secondary lithium ion battery is 100-500nm. In certain embodiments, the shell thickness of the composite material of the secondary lithium ion battery is 500-1000nm.
[0077] It should be understood that the "shell layer coated on the outer surface of the porous substrate" described herein does not mean that the shell layer material is only located on the outer side of the porous substrate. For example, the shell layer material may enter the pores of the porous substrate near the outer surface. For another example, the shell layer can be formed by reacting the outer layer of the porous substrate dispersed with nano-silicon.
[0078] It should also be understood that there may be a distinct interface between the shell layer and the porous matrix described herein. There may also be no distinct interface between the shell layer and the porous matrix described herein, for example, there is a boundary region with a certain thickness between the shell layer and the porous matrix.
[0079] It should also be understood that the shell layer described herein may have a uniform thickness at various locations or may have differences in thickness.
[0080] Preparation method
[0081] In another aspect, the present invention provides a method for preparing the composite material for a secondary lithium ion battery, the method comprising:
[0082] providing a porous matrix;
[0083] forming hydrogen-containing silicon dispersed in a porous matrix by a CVD deposition method and / or a liquid impregnation method;
[0084] The outer surface of the porous matrix in which the hydrogen-containing silicon is dispersed is coated to form a shell layer.
[0085] Provision of porous matrix
[0086] Herein, there is no particular limitation on the manner in which the porous matrix is provided, and the porous matrix may be obtained through commercial means or prepared by any preparation method in the art.
[0087] As an example, for porous carbon, pores can be introduced into the carbon material to form porous carbon in various ways. The pores in the carbon material can be controlled by adjusting the polymer precursor and / or processing conditions during the preparation process to produce the target porous carbon.
[0088] In the present invention, the preparation of porous materials includes but is not limited to the following methods: including emulsification, micelle generation, gasification, dissolution and then removal of solvent (for example, freeze drying), axial compaction and sintering, gravity sintering, powder rolling and sintering, isostatic compaction and sintering, metal spraying, metal coating and sintering, metal injection molding and sintering, etc.
[0089] As an example, for the porous polymer material, the preparation method thereof may include but is not limited to: preparing a porous gel by freeze drying.
[0090] Formation of hydrogenated silicon
[0091] Silicon can be dispersed into the pores of the porous matrix by any method known in the art to form hydrogenated silicon dispersed in the porous matrix. The retention of Si-H bonds can be achieved by controlling the silicon dispersion process (e.g., temperature), thereby effectively improving the stability of the composite material during the charge and discharge process and extending the battery cycle life.
[0092] The silicon dispersion process can be achieved by any method in the art, including but not limited to CVD deposition method and liquid impregnation method. Appropriate parameters in the dispersion process are helpful to obtain the desired composite material.
[0093] The process of forming hydrogen-containing silicon dispersed in a porous matrix by CVD deposition includes: placing the porous matrix in a reaction vessel, introducing a protective gas into the reaction vessel; heating the reaction vessel to a reaction temperature; introducing a silicon-containing gas into the reaction vessel to deposit in the porous matrix. The heating rate of the reaction vessel can be 1-10°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc. The reaction temperature can be 400-600°C, such as 400°C, 405°C, 420°C, 450°C, 480°C, 500°C, 550°C, 600°C, etc. The flow rate of the protective gas can be 5-30 L / min, such as 5 L / min, 10 L / min, 15 L / min, 20 L / min, 23 L / min, 25 L / min, 30 L / min, etc. The total flow rate of the silicon-containing gas can be 10-40 L / min, such as 10 L / min, 15 L / min, 20 L / min, 25 L / min, 30 L / min, 35 L / min, 40 L / min, etc. The deposition time can be 5-20 hours, such as 5 hours, 6 hours, 10 hours, 15 hours, 20 hours, etc.
[0094] In the CVD deposition method, the silicon-containing gas may include: dichlorosilane, Si n H 2n+2 Silane or a combination thereof, wherein n is an integer selected from 1 to 3. The silicon-containing gas may preferably include: dichlorosilane, monosilane, disilane, trisilane or a combination thereof.
[0095] In the CVD deposition method, the reaction vessel can be designed as a fluidized bed reactor, a tube furnace, a bell furnace, a pit furnace, a lifting kiln, a rotary kiln, a box kiln or other suitable reactor types. In a preferred embodiment, the reaction is carried out under conditions that provide uniform gas phase entry, such as a reactor in which the raw materials are fluidized, or stirred by other means to provide uniform gas entry.
[0096] Preferably, the composite material for secondary lithium-ion batteries provided by the present invention places the porous carbon particles in an inert atmosphere and at a high temperature, and fully contacts with a silicon-containing gas, so as to achieve uniform deposition of silicon via chemical vapor deposition, thereby generating hydrogen-containing silicon in the pores of the porous carbon. Specifically, the porous carbon is placed in a reaction vessel, and nitrogen or argon is introduced into the reaction vessel as a protective gas at a flow rate of 1-50L / min, and the reactor is heated to 400-600°C at a heating rate of 1-10°C / min. Then the silicon-containing gas is introduced into the reaction vessel and deposited on the porous carbon. Preferably, the temperature can be 400-450°C, or 450-500°C, or 500-550°C, or 550-600°C, or 500-600°C. The silicon-containing gas and the inert gas are introduced into the reaction container together, wherein the content of the silicon-containing gas can be 0.1-1%, 1%-10%, 10%-20%, 20%-30%, 30%-40%, or 40%-50%. The silicon-containing gas can also be any gas having the general formula Si n H 2n+2 (wherein n is an integer selected from 1-3) a gas of one or more silanes in the silane. For example, the silicon-containing gas can be monosilane, the silicon-containing gas can also be disilane, and the silicon-containing gas can also be trisilane. The reaction vessel can be designed as: a fluidized bed reactor, a tubular furnace, a bell furnace, a pit furnace, a lifting kiln, a rotary kiln, a box kiln or other suitable reactor types. In a preferred embodiment, the porous carbon particles are processed under conditions that provide uniform gas phase entry, such as a reactor in which the porous carbon particles are fluidized, or stirred by other means to provide uniform gas entry.
[0097] The process of forming hydrogen-containing silicon dispersed in a porous matrix by liquid impregnation includes: uniformly mixing the porous matrix and silane liquid, carbonizing and reducing at high temperature. Silane liquid includes: trichlorosilane, Si n H 2n+2 Silane or a combination thereof, wherein n is an integer selected from 4-10. In certain embodiments, the porous substrate to be impregnated or otherwise impregnated with silicon is porous carbon. The porous carbon to be impregnated or otherwise impregnated with silicon may include various carbon allotropes. For this reason, the porous carbon to be impregnated or otherwise impregnated with silicon may include graphite, nanographite, graphene, nanographene, carbon black, carbon nanowires, carbon nanotubes, etc. and combinations thereof.
[0098] In certain embodiments, a carbon scaffold impregnated or otherwise impregnated with silicon is removed to obtain a templated silicon material having desired dimensional characteristics. Removal of the scaffold carbon can be accomplished by means known in the art, such as by thermochemical activation under conditions where the silicon does not undergo undesirable changes in its electrochemical properties. Alternatively, if the scaffold is a porous polymer or other material soluble in a suitable solvent, the scaffold can be removed by dissolution.
[0099] Shell formation
[0100] The shell layer can be formed by coating the outer surface of the porous substrate in which hydrogen-containing silicon is dispersed. Coating the shell layer on the surface of the porous substrate in which hydrogen-containing silicon is dispersed can prevent the highly active hydrogen-containing silicon from being exposed to the air and oxidized. At the same time, during the use of the composite material, it can also reduce the direct contact between the porous substrate and the hydrogen-containing silicon therein and the electrolyte, helping to form a stable SEI film on the surface.
[0101] There is no special limitation on the coating method in this article. The outer surface of the porous substrate can be coated by reactive coating, adhesive coating, or a combination of reactive coating and adhesive coating. It can also be coated by other methods that can form a shell layer on the surface of the porous substrate dispersed with hydrogen-containing silicon.
[0102] Reactive coating means: forming a shell layer by reaction treatment to achieve coating. For example, the shell layer is formed by reaction treatment of a porous matrix dispersed with hydrogen-containing silicon. Specifically, the coating can be achieved by reaction treatment of partial oxidation, nitridation, and carbonization of hydrogen-containing silicon. In some embodiments, the shell material is silicon dioxide, which can be formed by placing the porous matrix dispersed with hydrogen-containing silicon in an oxidizing atmosphere for heat treatment, that is, a layer of silicon dioxide shell is uniformly generated on the surface of the porous matrix dispersed with hydrogen-containing silicon by surface oxidation. In these embodiments, the oxidizing atmosphere includes but is not limited to one or more of air, oxygen, carbon dioxide, carbon monoxide, water vapor, etc. The heat treatment temperature can be 0-100°C, 100-200°C, 200-300°C, 300-400°C, or 400-500°C.
[0103] Adhesive coating refers to attaching materials to the surface of a porous substrate to form a shell.
[0104] The outer surface of the porous substrate can be coated by combining reactive coating and adhesive coating. Specific examples are shown below.
[0105] In some embodiments, the shell material is carbon. A porous matrix (such as porous carbon) dispersed with hydrogen-containing silicon can be contacted with a carbon source precursor, and after heat treatment, a carbon shell layer is uniformly generated on the surface of the porous matrix dispersed with hydrogen-containing silicon. Coating methods include chemical vapor deposition (CVD), liquid phase coating, and solid phase coating. The following describes various coating methods using porous carbon as a porous matrix as an example. In the chemical vapor deposition (CVD) method, the carbon source precursor includes but is not limited to one or more of methane, propane, butane, cyclohexane, ethane, propylene and acetylene. The coating temperature can be 400-450°C, 450-500°C, 500-550°C, or 550-600°C. In the liquid phase coating method, the carbon source precursor includes but is not limited to one or more combinations of asphalt, polyvinyl alcohol, polyethylene glycol, anthracene, aniline, tannic acid, etc. The mixing ratio of the liquid carbon source to the porous carbon dispersed with hydrogenated silicon is in the range of 1:0.5-1:10, and the mixture is evenly mixed by stirring and ultrasonic dispersion. The carbonization temperature can be 400-450°C, 450-500°C, 500-550°C, or 550-600°C. In the solid-phase coating method, the carbon source precursor includes but is not limited to one or more combinations of glucose, sucrose, biphenyl, vinylpyrrolidone, etc. The carbonization temperature can be 400-450°C, 450-500°C, 500-550°C, or 550-600°C. The carbonization time can be 1 hour to 5 hours. The ratio of the solid carbon source to the porous carbon dispersed with hydrogenated silicon can be in the range of 1:0.5-1:10.
[0106] In some embodiments, the shell material is a metal oxide. The porous carbon dispersed with hydrogen-containing silicon is contacted with a metal oxide precursor, and a metal oxide shell is uniformly generated on the surface of the porous carbon dispersed with hydrogen-containing silicon through heat treatment. The coating method includes chemical vapor deposition (CVD), liquid phase coating, and solid phase coating. In these embodiments, the shell material precursor includes but is not limited to one or more of titanate, aluminum phosphate, etc., and the heat treatment temperature can be 0-100°C, 100-200°C, 200-300°C, 300-400°C, or 400-500°C.
[0107] In one embodiment, the present disclosure provides the preparation of a composite material for a secondary lithium ion battery, wherein the matrix is a porous matrix, and the uniform dispersion of silicon in the porous matrix is achieved by contacting the porous matrix with a silicon-containing reactant, and the silicon is mainly uniformly distributed in the form of hydrogenated silicon inside the pores of the porous matrix. The method may include the following steps:
[0108] 1) preparing a porous carbon material as a porous matrix; 2) subjecting the porous matrix to high temperature in a reaction vessel in the presence of a silicon-containing gas for deposition, thereby producing a porous carbon material in which hydrogen-containing silicon is uniformly dispersed.
[0109] In another embodiment, the present disclosure provides the preparation of a composite material for a secondary lithium ion battery, wherein the matrix is a porous matrix, the uniform dispersion of silicon in the porous matrix is achieved by contacting the porous matrix with a silicon-containing reactant, and the final coating layer is achieved by contacting the composite with a carbon-containing reactant. For example, the method may include the following steps: 1) preparing a porous carbon material as a porous matrix; 2) subjecting the porous matrix to high temperature deposition in a reaction vessel in the presence of a silicon-containing gas to produce a porous carbon material in which hydrogen-containing silicon is uniformly dispersed; 3) carbon coating is performed by any of gas phase coating, liquid phase coating, or solid phase coating.
[0110] In another embodiment, the present disclosure provides the preparation of a composite material for a secondary lithium ion battery, wherein the matrix is a porous matrix, the uniform dispersion of silicon in the porous matrix is achieved by contacting the porous matrix with a silicon-containing reactant, and the silicon dioxide coating is achieved by contacting the composite with an oxygen-containing atmosphere, and the carbon coating is achieved by contacting the composite with a carbon-containing reactant. For example, the method may include the following steps: 1) preparing a porous carbon material as a porous matrix; 2) subjecting the porous matrix to high temperature deposition in a reaction vessel in the presence of a silicon-containing gas to produce a porous carbon material in which hydrogen-containing silicon is uniformly dispersed; 3) treating the surface of the carbon material in which hydrogen-containing silicon is uniformly dispersed by any oxidizing atmosphere of air, carbon dioxide, and water vapor, and oxidizing and passivating to obtain a silicon dioxide shell layer; 4) carbon coating is performed by any one of gas phase coating, liquid phase coating, or solid phase coating to obtain a carbon shell layer. Properties of composite materials for secondary lithium-ion batteries able
[0111] The composite material of the present invention has various advantageous properties and can be used to prepare secondary lithium ion batteries with excellent performance.
[0112] Physical properties
[0113] The composite material for secondary lithium ion batteries of the present invention has suitable physical properties, which is conducive to preparing secondary lithium batteries with excellent performance.
[0114] Composite materials for secondary lithium-ion batteries can contain hydrogenated silicon in different proportions. Appropriate element content in the composite material helps to improve the performance of the composite material, especially the electrical performance.
[0115] Based on the total weight of the composite material, the hydrogen content in the hydrogen-containing silicon can be 0.01-10wt%, preferably 0.3-5wt%, and more preferably 0.9-3wt%, for example, 0.01wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, 5.0wt%, 10.0wt%, etc.
[0116] Based on the total weight of the composite material, the silicon content of the composite material can be 5-90wt%, preferably 15-70wt%, more preferably 30-65wt%, for example 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 37.9wt%, 40wt%, 40.2wt%, 42.5wt%, 45wt%, 46wt%, 46.1wt%, 47wt%, 47.2wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 60wt%, 65wt%, 70wt%, 80wt%, 85wt%, 90wt% and the like.
[0117] Based on the total weight of the composite material, the carbon content of the composite material can be 10-95wt%, preferably 30-90wt%, more preferably 35-85wt%, for example 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 42.5wt%, 45wt%, 46wt%, 7wt%, 48wt%, 49wt%, 50wt%, 50.8wt%, 51wt%, 51.3wt%, 51.8wt%, 52wt%, 53wt%, 54wt%, 55wt%, 57.3wt%, 60wt%, 60.3wt%, 65wt%, 70wt%, 80wt%, 90wt%, 95wt%, etc.
[0118] Based on the total weight of the composite material, the oxygen content of the composite material can be 0-3wt%, for example, 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc.
[0119] In certain embodiments, the C content in the composite material is 51.8wt%, the Si content is 45.0wt%, the O content is 0.2wt%, and the H content in the hydrogenated silicon is 3.0wt%. In certain embodiments, the C content in the composite material is 51.3wt%, the Si content is 46.1wt%, the O content is 0.2wt%, and the H content in the hydrogenated silicon is 2.4wt%. In certain embodiments, the C content in the composite material is 50.8wt%, the Si content is 47.2wt%, the O content is 0.2wt%, and the H content in the hydrogenated silicon is 1.8wt%. In certain embodiments, the C content in the composite material is 58.4wt%, the Si content is 40.2wt%, the O content is 0.2wt%, and the H content in the hydrogenated silicon is 1.2wt%. In certain embodiments, the C content in the composite material is 60.3wt%, the Si content is 37.9wt%, the O content is 0.3wt%, and the H content in the hydrogenated silicon is 1.5wt%. In certain embodiments, the C content in the composite material is 57.3 wt %, the Si content is 42.5 wt %, the O content is 0.2 wt %, and the H content in the hydrogenated silicon is 0.01 wt %.
[0120] The specific surface area of the composite material of the secondary lithium ion battery of the present invention may be different. The specific surface area BET of the composite material may be 1-10 m 2 / g, for example 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g. The total pore volume of the composite material can be 0.1cm 3 / g or less. In certain embodiments, BET is 1m 2 / g, the total pore volume is less than 0.1cm 3 / g. In certain embodiments, BET is 2m 2 / g, the total pore volume is less than 0.1cm 3 / g. In certain embodiments, BET is 4m 2 / g, the total pore volume is less than 0.1cm 3 / g. In certain embodiments, BET is 6m 2 / g, the total pore volume is less than 0.1cm 3 / g. In certain embodiments, BET is 8m 2 / g, the total pore volume is less than 0.1cm 3 / g. In certain embodiments, BET is 10m 2 / g, the total pore volume is less than 0.1cm 3 / g.
[0121] In a preferred embodiment, the size distribution of the composite material is relatively uniform, with an upper and lower limit in a preferred range, for example, a particle size distribution D50 of 1-15 μm and D100 of 10-30 μm. In certain embodiments, the composite material consists of the following size distribution: D50 of 5-20 μm and D100 of 20-40 μm. In certain embodiments, the composite material consists of the following size distribution: D50 of 15-25 μm and D100 of 40-60 μm; in certain embodiments, the composite material consists of the following size distribution: D50 of 20-30 μm and D100 of 50-70 μm. In certain embodiments, the composite material consists of the following size distribution: D50 of 25-35 μm and D100 of 60-80 μm. In certain embodiments, the composite material consists of the following size distribution: D50 of 30-40 μm and D100 of 70-90 μm. In certain embodiments, the composite material consists of the following size distribution: D50 is between 40-50 μm and D100 is between 80-100 μm.
[0122] In some embodiments, the XRD spectrum of the composite material of the secondary lithium ion battery has a peak with amorphous characteristics between 24-30°. In some embodiments, there is a sharp characteristic peak with a grain size of 5-30nm at 28°±0.5°. In certain embodiments, the grain size is 5nm. In certain embodiments, the grain size is 10nm. In certain embodiments, the grain size is 15nm. In certain embodiments, the grain size is 20nm. In certain embodiments, the grain size is 30nm.
[0123] The tap density of the composite material for secondary lithium battery of the present invention can be 0.5-2g / cm 3 In some embodiments, the composite material for a secondary lithium ion battery has a tap density of 0.5 g / cm 3 The tap density of the porous matrix is 0.2 g / cm 3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 0.6 g / cm 3 The tap density of the porous matrix is 0.3 g / cm 3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 0.8 g / cm 3 The tap density of the porous matrix is 0.4 g / cm 3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 1.2 g / cm3 The tap density of the porous matrix is 0.5 g / cm 3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 1.4 g / cm 3 The tap density of the porous matrix is 0.6 g / cm 3 In certain embodiments, the composite material for a secondary lithium ion battery has a tap density of 2 g / cm 3 The tap density of the porous matrix is 0.6 g / cm 3 .
[0124] Electrochemical performance
[0125] In certain embodiments, the electrochemical properties of the composite materials disclosed herein are tested in a half-cell. Among them, the preparation of the negative electrode pole piece: the composite material of the present application, the conductive additive carbon black, and the adhesive (1:1 sodium carboxymethyl cellulose and styrene-butadiene rubber) are weighed according to a mass ratio of 95:2:3, and the slurry is prepared in a pulper at room temperature. The prepared slurry is evenly coated on the copper foil, and after drying in a blast drying oven at 50°C for 2 hours, it is cut into pole pieces with a diameter of 8 mm. After the pole piece is vacuum-dried at 100°C in a vacuum drying oven for 10 hours, the dried pole piece is immediately transferred to a glove box for standby use for battery assembly. Assemble the battery: The assembly of the simulated battery is carried out in a glove box containing a high-purity Ar atmosphere, using metallic lithium as the counter electrode, and a solution of 1 mole of LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio v:v=1:1) as the electrolyte, and assembled into a battery. Test: A constant current charge and discharge mode test was performed using a charge and discharge instrument, with a discharge cut-off voltage of 0.005V and a charge cut-off voltage of 1.5V. The charge and discharge test was performed at a current density of C / 10. The composite material and commercial graphite were compounded in proportion to form a test material of 450mAh / g, which was assembled with lithium cobalt oxide into a button-type full battery, and cycled at 1C to evaluate its cycle performance.
[0126] In certain embodiments, the electrochemical performance of the composite material disclosed herein is tested in a button-type full cell. Among them, the preparation of the positive electrode sheet: formula parameters: 96.2% positive electrode material + 1.1% binder + 2.7% conductive agent; ingredient parameters: dry mixing, high-speed dispersion (solid content 72%), viscosity adjustment to a viscosity of about 5000 for coating; coating parameters: single-sided surface density 21mg / cm 2. After being cut into 15 cm wide strips, a positive electrode sheet with a size of 73 mm × 44 mm is obtained by die cutting. Preparation of negative electrode sheet: Formula parameters: 95.0 wt% negative electrode material (composite material sample of the embodiment) + 3.5 wt% binder (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) + 1.5 wt% conductive agent carbon black; Ingredient parameters: dry mixing and kneading (solid content 65%), high-speed dispersion (solid content 45%), viscosity adjusted to about 5000 for coating; Coating parameters: single-sided surface density 9 mg / cm 2 . After cutting into 15cm wide strips, the negative electrode sheets with a size of 75mm×46mm are obtained by die cutting. Assemble the battery: proceed as follows: Stacking: 9 negative electrode sheets and 8 positive electrode sheets are stacked in a Z shape; Welding the ears: The positive and negative electrodes are welded with ears respectively (positive electrode: aluminum; negative electrode: nickel); Hot pressing and cold pressing: hot pressing at 80℃ for 1min, cold pressing at room temperature for 1min; Aluminum mold punching: the punching depth is 3mm; Top sealing and side sealing: the heat sealing temperature is 190℃, and the heat sealing time is 6 seconds; Baking: keep warm at 95℃ for 3 days, during which nitrogen replacement is performed to ensure that the sample is in an inert atmosphere; Water content test: take The positive electrode and negative electrode are about 1g each, heated at 120℃ to remove water, and the water content is less than 200ppm; injection: 1 mol of LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio v:v=1:1) is the electrolyte, injected between the positive electrode and the negative electrode, and the injection coefficient calculated according to the first charge is 3.5; sealing: heat sealing temperature 190℃, heat sealing time 3 seconds, vacuum degree -90; soak at 45℃ for 2 days to obtain assembled battery samples. Cycle conditions for full battery test: 1C / 1C; voltage range: 2.8-4.25V.
[0127] The composite materials for secondary lithium-ion batteries disclosed herein can improve the properties of electrical storage devices, for example, have been shown to improve the first coulombic efficiency, charge specific capacity, and capacity retention of lithium-based batteries.
[0128] In one embodiment, when the composite material of the present invention is used as an electrode of a lithium-ion battery, the composite material has a first coulombic efficiency of 75% or more, or 80% or more, or 82% or more, or 85% or more, or 88% or more, or 90% or more, or 92% or more, or 93% or more, or 95% or more, or 98% or more, or 99% or more.
[0129] In one embodiment, when the composite material of the present invention is used as an electrode of a lithium ion battery, the composite material has a charge capacity of 1600 mAh / g or more, for example, 1600 mAh / g, 1650 mAh / g, 1680 mAh / g, 1700 mAh / g, 1750 mAh / g, 1800 mAh / g, 1850 mAh / g, 1900 mAh / g, 1950 mAh / g, 2000 mAh / g, 2100 mAh / g, 2200 mAh / g, etc.
[0130] In a certain embodiment, when the composite material of the present invention is used as an electrode of a lithium-ion battery, it runs for 15 cycles at 25°C and a 1C charge and discharge rate, and its capacity retention rate is above 40%, or above 60%, or above 80%, or above 85%. In a certain embodiment, when the composite material of the present invention is used as an electrode of a lithium-ion battery, it runs for 20 cycles at 25°C and a 1C charge and discharge rate, and its capacity retention rate is above 60%, or above 80%, or above 85%. In a certain embodiment, when the composite material of the present invention is used as an electrode of a lithium-ion battery, it runs for 50 cycles at 25°C and a 1C charge and discharge rate, and its capacity retention rate is above 80%, or above 85%. In a certain embodiment, when the composite material of the present invention is used as an electrode of a lithium-ion battery, it runs for 1000 cycles at 25°C and a 1C charge and discharge rate, and its capacity retention rate is above 80%, or above 85%. In one embodiment, when the composite material of the present invention is used as an electrode of a lithium-ion battery, the capacity retention rate is above 80% or above 85% after 1200 cycles at 25°C and 1C charge and discharge rate.
[0131] In some embodiments, in the test of lithium ion half-cells prepared from the composite materials of secondary lithium ion batteries of the present invention, the charging curve has no obvious platform at 0.4-0.5V, and the characteristic peak intensity at 0.4-0.5V of the DQ / DV curve is low. In certain embodiments, in the test of lithium ion half-cells prepared from the composite materials of secondary lithium ion batteries, the charging curve has a platform at 0.4-0.5V, and the characteristic peak intensity at 0.4-0.5V of the DQ / DV curve is high.
[0132] The platform of the charging curve at 0.4-0.5V and the characteristic peak of the corresponding DQ / DV curve at 0.4-0.5V are related to the crystallinity of hydrogenated silicon. The higher the crystalline silicon content, the more obvious the platform of the charging curve at 0.4-0.5V, and the stronger the characteristic peak intensity of the DQ / DV curve at 0.4-0.5V.
[0133] The composite materials for secondary lithium-ion batteries disclosed herein can improve the properties of electrical storage devices, for example, it has been shown that the expansion rate of the pole pieces of lithium-based batteries can be reduced. The thickness expansion rate test can be carried out in the following manner: Initial thickness calibration: 1. After the battery is capacitated, the battery is clamped and fully charged and discharged at 0.2C to calibrate the capacity and determine its actual initial discharge capacity; 2. Charge for 2.5 hours at the initial discharge capacity of 0.2C and adjust the SOC to 50%; 3. Disassemble the clamp and test the initial thickness of the battery at 50% SOC; 4. The soft pack thickness test is tested with a caliper, and the thickness in the middle of the battery is measured until a relatively stable thickness appears, which is recorded as T0. Full charge thickness expansion test: 1. During the cycle, the full charge thickness is tested every 50Cl for the first 200Cl of the battery and every 100Cl after 200Cl until the capacity decays to 80%; 2. Full charge is carried out according to the 0.2C CC 4.25V, 4.25V CV 0.04C process; 3. The soft pack thickness test is tested with a caliper, and the thickness in the middle of the battery is measured until a relatively stable thickness appears, which is recorded as Tn; 4. The thickness expansion of a specific number of cycles can be calculated according to the formula Tn / T0-1.
[0134] In one embodiment, when the composite material of the present invention is used as an electrode of a lithium-ion battery, it runs 1200 cycles at 25°C and 1C charge and discharge rate, and its electrode expansion rate is below 15%, or below 10%, or below 8%, for example, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, etc.
[0135] Beneficial Effects
[0136] In the existing technology, silicon nanotechnology still has certain shortcomings: on the one hand, nano-silicon is difficult to disperse evenly and is easy to agglomerate, which makes it impossible to give full play to the advantages of nano-silicon; on the other hand, nano-silicon has high activity and consumes a large amount of lithium ions in the formation process of solid electrolyte interface (SEI) film, which reduces the coulomb efficiency; at the same time, during use, the surface of nano-silicon contacts and reacts with the electrolyte, resulting in gas production, which causes battery capacity decay, cycle performance reduction, and even safety problems. Therefore, the application of nano-silicon in secondary lithium-ion batteries still faces huge challenges.
[0137] The present invention provides a preparation method and application of a composite material for a secondary lithium ion battery. Compared with the prior art, in the composite material of the present invention, the porous matrix has a rich pore structure, the nano silicon is hydrogen-containing silicon, which is uniformly dispersed in the inner pores of the porous matrix, and the outer surface layer of the porous matrix is free of silicon, and the outermost layer of the material also includes a dense carbon shell. The present invention uses a variety of silicon-containing precursors and porous matrix as raw materials, uniformly disperses silicon in the porous matrix, and controls the temperature so that silicon retains a part of Si-H bonds to form hydrogen-containing silicon. Finally, the whole material is carbon-coated to avoid spontaneous combustion of highly active nano hydrogen-containing silicon in the air, and at the same time, it is also ensured that the material does not directly contact the electrolyte during use, and it is easy to form a stable SEI film. On the one hand, the present invention uniformly disperses hydrogen-containing silicon in the composite material, solves the dispersion problem of silicon, and avoids the volume effect caused by agglomeration of silicon during charging and discharging; on the other hand, the Si-H bonds contained in hydrogen-containing silicon can effectively improve the stability of the material structure during charging and discharging, and extend the battery cycle life.
[0138] The method for preparing the composite material for secondary lithium ion batteries provided by the present invention is simple and easy to operate, and can be applied to batch production.
[0139] Example
[0140] The present invention is further described in detail below by specific examples, but it should be understood that these examples are only used for more detailed description, and should not be understood as limiting the present invention in any form, that is, it is not intended to limit the scope of protection of the present invention. Unless otherwise specified, the instruments and reagents used herein are all commercially available. The porous carbon used in the examples of the present application is prepared according to the conventional methods of the art.
[0141] Sample preparation
[0142] Example 1: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.8-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 405°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 405°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 1.
[0143] Example 2: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.8-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 420°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 420°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 2.
[0144] Example 3: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.8-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 3.
[0145] Example 4: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.8-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 480°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 480°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 4.
[0146] Example 5: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.8-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 500°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 500°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 5.
[0147] Example 6: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 550°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 550°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 6.
[0148] Example 7: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 600°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 600°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 7.
[0149] Example 8: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1000-1100 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.4-0.6cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 405°C at a heating rate of 5°C / min. Silicon-containing gas monosilane was then introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 405°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 8.
[0150] Example 9 uses porous carbon with the following parameters as the porous matrix: oxygen content of 0.01-0.4 mmol / g, and BET of 1500-1600 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.6-0.8cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 9.
[0151] Example 10: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 2200-2500 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 1.0-1.2cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas at a nitrogen flow rate of 27L / min. The tubular furnace was heated to 450°C at a heating rate of 5°C / min. Silicon-containing gas monosilane was then introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 50L / min and the deposition time was 4 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, acetylene gas was introduced at a flow rate of 15L / min, and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 10.
[0152] Example 11: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 1-5μm, D100 is 10-20μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The material was carbon-coated by gas phase coating to obtain the composite material sample of Example 11.
[0153] Example 12: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 10-12μm, D100 is 15-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Then, silicon-containing gas monosilane was introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min, and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min, and the duration was 2 hours. The above-mentioned composite material was carbon-coated by gas phase coating to obtain the composite material sample of Example 12.
[0154] Example 13: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 12-15μm, D100 is 20-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Silicon-containing gas monosilane was then introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The above-mentioned composite material was carbon-coated by gas phase coating to obtain the composite material sample of Example 13.
[0155] Example 14: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.01-0.4 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 15-20μm, D100 is 25-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Silicon-containing gas monosilane was then introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The above-mentioned composite material was carbon-coated by gas phase coating to obtain the composite material sample of Example 14.
[0156] Example 15: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.1-0.3 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas at a flow rate of 23L / min. The tubular furnace was heated to 450°C at a heating rate of 5°C / min. Silicon-containing gas monosilane was then introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced at a flow rate of 15L / min for 2 hours. The above-mentioned composite material was carbon-coated by gas phase coating to obtain the composite material sample of Example 15.
[0157] Example 16: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.2-0.5 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Silicon-containing gas monosilane was then introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min, and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min, and the duration was 2 hours. The above-mentioned composite material was carbon-coated by gas phase coating to obtain the composite material sample of Example 16.
[0158] Example 17: A porous carbon having the following parameters is used as the porous matrix: an oxygen content of 0.3-0.6 mmol / g and a BET of 1900-2000 m 2 / g, particle size distribution D50 is 5-10μm, D100 is 20-50μm, and total pore volume is 0.9-1.0cm 3 / g. 12kg of porous carbon was placed in a fluidized bed, and nitrogen was introduced as a protective gas. The nitrogen flow rate was 23L / min, and the tubular furnace was heated to 450°C at a heating rate of 5°C / min. Silicon-containing gas monosilane was then introduced into the fluidized bed and deposited on the porous carbon. The monosilane gas flow rate was 35L / min and the deposition time was 6 hours. After the deposition was completed, the reaction temperature was maintained at 450°C, and acetylene gas was introduced. The flow rate of acetylene gas was 15L / min and the duration was 2 hours. The above-mentioned composite material was carbon-coated by gas phase coating to obtain the composite material sample of Example 17.
[0159] Performance Testing
[0160] Infrared: The composite material sample powder of the embodiment is mixed with potassium bromide powder and then pressed into tablets at a pressure of 8-10 MPa for 1 minute. The prepared pressed tablet samples are placed in a Fourier infrared spectrometer for testing. The infrared absorption characteristics corresponding to the silicon-hydrogen bonding mode generally have three regions in the infrared absorption spectrum: (I) 500-800 cm -1 Rocking mode region, (II) 800-1000cm -1 Bending mode region, (III) 1850-2250cm -1 The stretching mode area; the characteristic peak I signal is stronger, and the latter two characteristic absorption peaks are related to the preparation conditions. The hydrogen content can be calculated by the rocking mode calculation method. -1 The absorption peak at the position is Gaussian fitted, and the hydrogen content C in the hydrogen-containing silicon in the composite material is determined by the integral area of the fitting function. H , the specific data are shown in the following Table 1.
[0161] Figure 1 (a)-(g) show the infrared spectra of the composite material samples of Examples 1-7, respectively. Figure 1 As shown in (a), in the infrared spectrum of the sample of Example 1, 630 cm -1 The absorption peak near 1050cm is attributed to the swing vibration absorption of Si-H bond. -1 The absorption peak near 1384cm is attributed to the stretching vibration absorption of carbon-oxygen bond. -1 The absorption peak near 1630cm is attributed to the stretching vibration absorption of carbon-hydrogen bonds. -1 The absorption peak near 2370cm is attributed to the stretching vibration absorption of carbon-carbon bonds. -1 The nearby absorption peak is attributed to the asymmetric stretching vibration absorption of the carbon-oxygen bond.
[0162] XRD: The sample powder of the composite material of the embodiment is placed in an XRD diffractometer at 10-65°, 5° / min, and the difference between the peaks of crystal and amorphous silicon is compared. The grain size can also be fitted at the same time. The X-ray uses a copper target with a wavelength of 0.154nm.
[0163] SEM: used to characterize the surface morphology of composite materials, observe the surface roughness, and assist in determining the deposition of surface silicon.
[0164] TEM: The electron beam emitted by the electron gun passes through the condenser along the optical axis of the mirror in the vacuum channel, and is converged by the condenser into a sharp, bright and uniform light spot, which is irradiated on the sample in the sample chamber; the electron beam after passing through the sample carries the internal structural information of the sample, and the amount of electrons passing through the dense part of the sample is small, and the amount of electrons passing through the sparse part is large; after the convergence and focusing of the objective lens and the primary magnification, the electron beam enters the lower intermediate lens and the first and second projection mirrors for comprehensive magnification and imaging. Finally, the magnified electron image is projected on the fluorescent screen in the observation room. Disperse the composite material powder evenly in ethanol, take a small amount and drop it on the copper mesh, and inject it after it is dried. The size of the silicon domain in the composite material can be observed by TEM.
[0165] The XRD spectrum of the composite material sample of Example 1 is as follows: Figure 2 As shown. Figure 2 It can be seen that the hydrogenated silicon deposited at this temperature is in an amorphous state, the peak between the diffraction angle of 20-30° is relatively broad, and no sharp diffraction response peak attributable to the crystalline silicon (111) plane is found near 28.4°.
[0166] Figure 3 (a) shows a SEM image of the composite material sample of Example 1. Figure 3 (b) shows a TEM image of the composite material sample of Example 1. Figure 3 It can be seen that the surface of the composite material obtained under this preparation condition is not significantly different from the surface of the porous carbon substrate without silicon deposition, showing a uniform rough structure, and no granular nano-silicon deposition was found. TEM characterization of the near-surface area of the material did not find obvious diffraction stripes attributed to crystalline Si, proving that the hydrogenated silicon deposited at this temperature is in an amorphous state.
[0167] According to the test results of XRD, SEM and TEM, in the samples of all embodiments, the deposited hydrogen-containing silicon is in an amorphous state.
[0168] Element analysis: For the composite material samples of the embodiment, the C content was measured by a carbon-sulfur analyzer, the O content was measured by a nitrogen-oxygen analyzer, and the hydrogen content C in hydrogen-containing silicon was H The infrared absorption peak fitting calculation in the rocking mode region was adopted, and the content of components other than C, O, and H was taken as the Si content in the composite material sample. The specific data are shown in Table 1 below.
[0169] Electrical performance test
[0170] Half-cell:
[0171] The composite material sample of the embodiment was used to prepare the negative electrode sheet, and button-type half-cells were assembled for testing, as follows:
[0172] Preparation of negative electrode sheet: The composite material sample of the embodiment, the conductive additive carbon black, and the binder (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) were weighed in a mass ratio of 95:2:3 and slurry was prepared in a pulper at room temperature. The prepared slurry was evenly coated on the copper foil, dried in a blast drying oven at 50°C for 2 hours, cut into 8mm diameter electrode sheets, and vacuum dried in a vacuum drying oven at 100°C for 10 hours. The dried electrode sheets were then transferred to the glove box for standby use for battery assembly.
[0173] Assembling the battery: The simulated battery was assembled in a glove box containing a high-purity Ar atmosphere. Metallic lithium was used as the counter electrode and a solution of 1 mol of LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio v:v=1:1) was used as the electrolyte to assemble the battery.
[0174] Half-cell test: A constant current charge and discharge mode test was performed using a charge and discharge instrument. The discharge cut-off voltage was 0.005 V, the charge cut-off voltage was 1.5 V, and the charge and discharge test was performed at a current density of C / 10. The relevant test data obtained (charge specific capacity, first coulomb efficiency, etc.) are detailed in Table 1.
[0175] The charge and discharge curves of the button-type half-cell obtained by assembling the negative electrode sheet prepared from the composite material sample of Example 1 are as follows: Figure 4 As shown in Figure 2, the first discharge (lithium insertion) curve has three platforms at 0.3-0.5V, 0.1-0.3V and 0-0.1V, corresponding to the three lithium insertion peaks in the DQ / DV curve. The lithium insertion peak at 0.3-0.5V is related to the microporous structure and oxygen content of the porous carbon substrate, and the lithium insertion peak at 0.1-0.3V corresponds to Si→Li 2.0 Si alloy phase transition; 0-0.1V lithium insertion peak corresponds to Li 2.0 Si→Li 3.5 Si alloy phase transition; the first charge (delithiation) curve has three platforms at 0.2-0.4V, 0.4-0.6V and 0.6-0.8V, corresponding to the three delithiation peaks in the DQ / DV curve, among which the delithiation peak at 0.2-0.4V corresponds to Li 3.5 Si→Li 2.0 The alloy phase transition of Si, the delithiation peak of 0.4-0.6V corresponds to Li 2.0 The alloy phase transition of Si→Si, the delithiation peak at 0.6-0.8V is related to the microporous structure and oxygen content of the porous carbon substrate. In the DQ / DV curves of some other embodiments, there is also a sharp delithiation peak between 0.4-0.5V, the intensity of which is related to the content of crystalline silicon. The higher the content of crystalline silicon, the greater the peak intensity.
[0176] Full Battery:
[0177] Referring to the preparation and testing process of the above half-cell, the composite material sample of the embodiment is used as the negative electrode material to prepare a negative electrode sheet, and a full battery is assembled and tested, as follows:
[0178] Preparation of positive electrode sheet: Formula parameters: 96.2wt% LiNi 0.6 Co 0.2 Mn 0.2 O2 (622 positive electrode material) + 1.1wt% PVDF (binder) + 2.7wt% Super P (conductive agent); batching parameters: dry mixing, high-speed dispersion (solid content 72%), viscosity adjusted to about 5000cP for coating; coating parameters: single-sided surface density 21mg / cm 2 After being cut into 15 cm wide strips, the positive electrode sheets with a size of 73 mm × 44 mm were obtained by die cutting.
[0179] Preparation of negative electrode sheet: formula parameters: 95.0wt% negative electrode material (composite material sample of the embodiment) + 3.5wt% binder (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) + 1.5wt% conductive agent carbon black; ingredient parameters: dry mixing and kneading (solid content 65%), high-speed dispersion (solid content 45%), viscosity adjustment to about 5000 for coating; coating parameters: single-sided surface density 9mg / cm 2 After being cut into 15 cm wide strips, the negative electrode sheets with a size of 75 mm × 46 mm were obtained by die cutting.
[0180] Assemble the battery: proceed as follows: stacking: stack 9 negative electrode sheets and 8 positive electrode sheets in a Z shape; welding the tabs: weld the tabs on the positive and negative electrodes respectively (positive electrode: aluminum; negative electrode: nickel); hot pressing and cold pressing: hot pressing at 80°C for 1 minute and cold pressing at room temperature for 1 minute; aluminum mold punching: the punching depth is 3mm; top sealing and side sealing: the heat sealing temperature is 190°C and the heat sealing time is 6 seconds; baking: keep warm at 95°C for 3 days, during which nitrogen replacement is performed to ensure that the sample is in an inert atmosphere; water content test: take The positive electrode and negative electrode pieces, each weighing about 1g, are heated at 120°C to remove water to make the moisture content less than 200ppm; liquid injection: a solution of 1 mol of LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio v:v=1:1) is used as the electrolyte and injected between the positive electrode and the negative electrode, and the liquid injection coefficient calculated according to the first charge is 3.5; sealing: heat sealing temperature is 190°C, heat sealing time is 3 seconds, and vacuum degree is -90; soak at 45°C for 2 days to obtain the assembled battery sample.
[0181] Full battery test: Cycle conditions: 1C / 1C; Voltage range: 2.8-4.25V.
[0182] Figure 5 The cycle curves of the button-type full cells of Examples 1-7 are shown (number of cycles: 50). Figure 6 The cycle curve of the coin-type full cell of Example 1 is shown (number of cycles: 1200).
[0183] Thickness expansion test:
[0184] Initial thickness calibration: 1. Put the battery after capacity separation on the fixture, calibrate the capacity once with 0.2C full charge and discharge, and determine its actual initial discharge capacity; 2. Charge for 2.5 hours at 0.2C according to the initial discharge capacity, and adjust the SOC to 50%; 3. Remove the fixture and test the initial thickness of the battery at 50% SOC; 4. Use a caliper to test the thickness of the soft pack, and measure the thickness in the middle of the battery until a relatively stable thickness appears, which is recorded as T0.
[0185] Full charge thickness expansion test: 1. During the cycle, the full charge thickness is tested every 50Cl for the first 200Cl of the battery and every 100Cl after 200Cl until the capacity decays to 80%; 2. Full charge is carried out according to the 0.2C CC 4.25V, 4.25V CV 0.04C process; 3. The soft pack thickness test is tested with a caliper, and the thickness in the middle of the battery is measured until a relatively stable thickness appears, which is recorded as Tn; 4. The thickness expansion of a specific number of cycles can be calculated according to the formula Tn / T0-1.
[0186] Figure 7 The thickness expansion curve of the button-type full battery of Example 1 is shown.
[0187] Table 1
[0188]
[0189] H content*: hydrogen content C in hydrogenated silicon H .
[0190] like Figure 5 As shown, the button-type full battery prepared by the composite materials of Examples 1-7 of the present application has excellent long cycle retention rate. Under the working conditions of 25°C and 1C charge and discharge rate, the capacity retention rate is above 40% after 15 cycles. Figure 5 It can be seen that the capacity retention rate is positively correlated with the hydrogen content in the hydrogenated silicon in the composite material. The hydrogen content in the hydrogenated silicon in the composite material sample of Example 6 increased to 0.03wt%. The button-type full battery prepared from the sample of Example 6 was operated for 20 cycles at 25°C and 1C charge and discharge rate, and its capacity retention rate was still above 60%. For the composite material samples of Examples 1-5, the hydrogen content in the hydrogenated silicon in the samples was above 0.09%, and the long cycle retention rate of the button-type full battery prepared was significantly better. Under the working conditions of 25°C and 1C charge and discharge rate, the capacity retention rate was above 80% after 50 cycles.
[0191] The full battery prepared using the composite material of Example 1 exhibits a very excellent long cycle retention rate. Under the working conditions of 25°C and 1C charge and discharge rate, the capacity retention rate reaches 87% after 1200 cycles, which is much higher than the 80% capacity retention rate requirement of the power battery after 1000 cycles. In terms of the pole piece expansion rate, the button-type full battery of Example 1 has an expansion rate of only 8% after 1000 cycles.
[0192] In the composite material samples of Example 3 and Examples 8-10, except for the silicon content, the other element contents, BET and particle size distribution are very similar. As shown in Table 2, as the silicon content of the composite material sample increases, the charge specific capacity of the sample shows an upward trend.
[0193] From the preparation process of Examples 8-10, it can be seen that the silicon content of the composite material sample is positively correlated with the pore volume of the porous carbon matrix (such as BET test results). From the preparation process of Examples 11-14, it can be seen that the silicon content of the composite material sample is negatively correlated with the particle size of the porous carbon matrix (such as D50 particle size).
[0194] In the samples of Example 1 and Examples 15-17, except for the oxygen content, the other element contents, BET and particle size distribution are very similar. As shown in Table 2, as the oxygen content of the composite material sample increases, the first coulomb efficiency of the sample shows a slowly decreasing trend.
[0195] Table 1 and Figure 5 It can be seen from the test data that the battery assembled with the composite material for secondary lithium-ion batteries according to the embodiment of the present invention has a higher charge capacity and first coulomb efficiency than the negative electrode on the market, and the cycle performance is also significantly improved.
[0196] In the composite material of the present invention, the porous matrix has a rich pore structure, the nano silicon is hydrogen-containing silicon, which is uniformly dispersed in the inner pores of the porous matrix, and the outer surface of the porous matrix is silicon-free, and the outermost layer of the material also includes a dense shell layer. The present invention uses a variety of silicon-containing precursors and porous matrix as raw materials, uniformly disperses silicon in the porous matrix, and controls the temperature so that silicon retains a part of Si-H bonds to form hydrogen-containing silicon. Finally, the whole material is coated to prevent the highly active nano hydrogen-containing silicon from spontaneous combustion in the air, and at the same time, it is ensured that the material does not directly contact the electrolyte during use, and a stable SEI film is easily formed.
[0197] On the one hand, the present invention evenly disperses hydrogen-containing silicon in a porous matrix, thereby solving the silicon dispersion problem and avoiding the volume effect caused by silicon agglomeration during the charge and discharge process; on the other hand, the Si-H bonds contained in hydrogen-containing silicon can effectively improve the stability of the material structure during the charge and discharge process and extend the battery cycle life.
[0198] It will be clear to those skilled in the art that many modifications and variations of the present invention may be made without departing from its spirit and scope. The specific embodiments described herein are provided only by way of example and are not intended to be limited in any way. The true scope and spirit of the present invention are shown by the appended claims, and the description and examples are merely exemplary.
Claims
1. A composite material for a secondary lithium-ion battery, characterized in that: The composite material comprises: a porous matrix, hydrogen-containing silicon dispersed in the porous matrix, and a shell layer coated on the outer surface of the porous matrix; The hydrogen-containing silicon is all nano-silicon particles dispersed in the porous matrix, and at least a portion of the nano-silicon particles have Si—H bonds.
2. The composite material according to claim 1, characterized in that In the composite material, based on the total weight of the composite material, the hydrogen content in the hydrogen-containing silicon is 0.01-10 wt %, preferably 0.3-5 wt %, and more preferably 0.9-3 wt %.
3. The composite material according to claim 1, characterized in that Based on the total weight of the composite material, the silicon content of the composite material is 5-90wt%, preferably 15-70wt%, more preferably 30-65wt%; and / or Based on the total weight of the composite material, the carbon content of the composite material is 10-95wt%, preferably 30-90wt%, more preferably 35-85wt%; and / or The oxygen content of the composite material is 0-3 wt % based on the total weight of the composite material.
4. The composite material according to claim 1, characterized in that The tap density of the composite material is 0.5-2 g / cm 3 ; and / or The tap density of the porous matrix is 0.2-0.6 g / cm 3 .
5. The composite material according to claim 1, characterized in that The particle size of the hydrogen-containing silicon is in the range of 0.1-60 nm, preferably 0.1-20 nm, and more preferably 1-5 nm.
6. The composite material according to claim 1, characterized in that The composite material has one or more of the following characteristics: The specific surface area of the composite material is 10 m 2 / g or less; The total pore volume of the composite material is 0.1 cm 3 / g or less; The particle size D50 of the composite material is 1-50 μm; The D100 particle size of the composite material is 10-100 μm.
7. The composite material according to claim 1, characterized in that The porous matrix has one or more of the following characteristics: The oxygen content of the porous matrix is 0.01-0.6 mmol / g; The porous matrix contains 20%-90% micropores, 10%-50% mesopores and 0-30% macropores; the specific surface area of the porous matrix is 1000-2500m 2 / g; The total pore volume of the porous matrix is 0.1-2.5 cm 3 / g, preferably 0.5-1.2cm 3 / g; The D50 particle size of the porous matrix is 1-30 μm, preferably 1-20 μm; The D100 particle size of the porous matrix is 5-80 μm, preferably 5-50 μm.
8. A method for preparing the composite material according to any one of claims 1 to 7, comprising the following steps: providing a porous matrix; forming hydrogen-containing silicon dispersed in a porous matrix by a CVD deposition method and / or a liquid impregnation method; The outer surface of the porous matrix in which the hydrogen-containing silicon is dispersed is coated to form a shell layer.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the composite material according to any one of claims 1 to 7.
10. A lithium ion secondary battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Preparation method of silicon-carbon composite material, silicon-carbon composite material and battery
CN116454256A
Silicon-carbon composite and method
CN114287072A
Porous silicon carbon-based composite material and preparation method thereof, negative electrode and lithium ion battery
CN116779816A
Silicon-based negative electrode material and preparation method thereof
CN116914112A
Manufacturing process for a silicon-carbon composite
DE102014211012A1